Development of Stored-Product Moths on Cricket Powder and Insect-Enriched Biscuits - Serena Malabusini (Foods, 2025)
In recent years, interest in edible insects has increased in Western countries, leading to an expansion of the market for insect-based products. In this context, it is essential to assess their susceptibility to infestation by stored-product pests, to ensure food safety and to develop appropriate storage management strategies. This study examined the ability of three common stored-product moth species (Plodia interpunctella, Corcyra cephalonica and Ephestia kuehniella) to infest Acheta domesticus powder and biscuits enriched with cricket powder. Larval development, adult emergence, wingspan and female fertility were evaluated. The results showed that P. interpunctella and C. cephalonica were able to complete their development on cricket powder, albeit with lower survival rates, longer developmental times and fewer offspring than on the standard diet. E. kuehniella was unable to develop on cricket powder and only minimal adult emergence was recorded in the biscuit trials, although signs of infestation were detected. These findings demonstrate that stored-product moths represent a potential infestation risk for this novel food, the market for which is expected to grow.